Application of Immobilized Glucose Oxidase in Iron Oxide Nanoparticles in Cotton Bleaching – An Ecofriendly Approach and Greener Alternative - Kalyani, G.; Jananiniveda, E.; Koushika, S.; Rajesh, E.M. (International Journal of Scientific Research in Biological Sciences, 2019)
Cotton, a natural textile fiber that naturally exists with impurities and yellowish color until bleaching that imparts whiteness to the fabrics. In this current research, iron oxide nanoparticles were synthesized and immobilized with microbially produced glucose oxidase which visualized by scanning electron microscope showed 62 and 112 nm respectively. Conventional and bio-bleaching of desized fabrics was done efficiently. Weight loss and water absorbency results of bio-bleached fabrics had shown higher effect than conventional whereas vice-versa in tensile strength. To ensure the quality of bleaching, whiteness index was performed and showed 65.21, 67.14 and 69.12 that corresponds for conventional and bio-bleached fabrics. Recyclability of immobilized glucose oxidase enzyme was showed better usage for 2 cycles which were enclosed by the comparison of whiteness index. Hence, we conclude that immobilized enzymatic bleaching showed significance which lacks in control and free enzyme treated fabrics.